Progress towards a clinically-successful ATR inhibitor for cancer therapy - Barnieh, Francis M.; Loadman, Paul M.; Falconer, Robert A. (Current research in pharmacology and drug discovery, 2021)
The DNA damage response (DDR) is now known to play an important role in both cancer development and its treatment. Targeting proteins such as ATR (Ataxia telangiectasia mutated and Rad3-related) kinase, a major regulator of DDR, has demonstrated significant therapeutic potential in cancer treatment, with ATR inhibitors having shown anti-tumour activity not just as monotherapies, but also in potentiating the effects of conventional chemotherapy, radiotherapy, and immunotherapy. This review focuses on the biology of ATR, its functional role in cancer development and treatment, and the rationale behind inhibition of this target as a therapeutic approach, including evaluation of the progress and current status of development of potent and specific ATR inhibitors that have emerged in recent decades. The current applications of these inhibitors both in preclinical and clinical studies either as single agents or in combinations with chemotherapy, radiotherapy and immunotherapy are also extensively discussed. This review concludes with some insights into the various concerns raised or observed with ATR inhibition in both the preclinical and clinical settings, with some suggested solutions. [Display omitted] •The DNA Damage Response (DDR) is of significant interest in cancer research.•ATR kinase is a promising target for cancer therapeutics and drug discovery.•ATR kinase inhibitors have recently begun evaluation in cancer clinical trials.•First comprehensive review of the history and current status of ATR inhibitor development.